Assessing mentoring : a scoping review of mentoring assessment tools in internal medicine between 1990 and 2019 - Ng, Yong Xiang (2021)
Background: Mentoring's success in enhancing a mentee's professional and personal development, and a host organisations' reputation has been called into question, amidst a lack of effective tools to evaluate mentoring relationships and guide oversight of mentoring programs. A scoping review is proposed to map available literature on mentoring assessment tools in Internal Medicine to guide design of new tools. Objective: The review aims to explore how novice mentoring is assessed in Internal Medicine, including the domains assessed, and the strengths and limitations of the assessment methods. Methods: Guided by Levac et al.’s framework for scoping reviews, 12 reviewers conducted independent literature reviews of assessment tools in novice mentoring in PubMed, Embase, Scopus, ERIC, Cochrane, GreyLit, Web of Science, Open Dissertations and British Education Index databases. A ‘split approach’ saw research members adopting either Braun and Clarke’s approach to thematic analysis or directed content analysis to independently evaluate the data and improve validity and objectivity of the findings. Results: 9662 abstracts were identified, 187 full-text articles reviewed, and 54 full-text articles included. There was consensus on the themes and categories identified through the use of the split approach, which were the domains assessed and methods of assessment. Conclusion: Most tools fail to contend with mentoring’s evolving nature and provide mere snap shots of the mentoring process largely from the mentee’s perspective. The lack of holistic, longitudinal and validated assessments propagate fears that ethical issues in mentoring are poorly recognized and addressed. To this end, we forward a framework for the design of ‘fit for purpose’ multi-dimensional tools.